College Sexual Assault and Campus Climate for Sexual- and Gender-Minority Undergraduate Students - Coulter, Robert W. S.; Rankin, Susan R. (Journal of interpersonal violence, 2020)
Sexual- and gender-minority (e.g., lesbian, gay, bisexual, and transgender) undergraduate students are at greater risk for sexual assault victimization than their cisgender (i.e., nontransgender) heterosexual peers. However, few studies have examined how social environments affect sexual assault victimization among sexual- and gender-minority undergraduate students. Nevertheless, this research area was identified as a priority by the Institute of Medicine as well as President Barack Obama’s White House Task Force to Protect Students From Sexual Assault. Therefore, we tested the association between college campuses’ inclusion of sexual- and gender-minority people and experiences of sexual assault victimization. Cross-sectional surveys were completed by sexual- and gender-minority undergraduate students (N = 1,925) from higher education institutions in all 50 U.S. states in 2010. Our dependent variable was experiencing sexual assault victimization at college. Our primary independent variable was campus climate, measured with items assessing perceived inclusion of sexual- and gender-minority people and witnessing sexual- or gender-minority harassment. We used multivariable logistic regression with generalized estimating equations (accounting for the clustering of students within schools) to estimate the association between campus climate and experiencing sexual assault victimization. Overall, 5.2% of the sample reported ever being victims of sexual assault at college. Controlling for sexual orientation, gender identity, race/ethnicity, and year in school, greater perceived inclusion of sexual- and gender-minority people on campus was associated with significantly lower odds of experiencing sexual assault victimization. Our study suggests that improving campus climate for sexual- and gender-minority individuals may reduce their prevalence of college sexual assault, which has potential implications for college practitioners and administrators as well as sexual assault prevention programs and policies.